2018
DOI: 10.1002/ajmg.a.40666
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and phenotype correlations for SHANK3 de novo mutations in neurodevelopmental disorders

Abstract: SHANK3 has been identified as the causative gene of 22q13.3 microdeletion syndrome phenotype. De novo mutations (DNMs) of SHANK3 were subsequently identified in patients with several neurodevelopmental disorders, including autism spectrum disorders (ASDs), schizophrenia (SCZ), a Rett syndrome-like phenotype, and intellectual disability (ID). Although broad developmental phenotypes of these patients have been described in single studies, few studies have reviewed the genotype and phenotype relationships using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…This SHANK3 splicing mutation has been previously reported by (Li et al, ). SHANK3 variants named according to the SHANK3 RefSeq mRNA (NM_033517.1) and protein (NP_277052.1) sequence, in which the exon 11 sequence has been corrected.…”
Section: Methodssupporting
confidence: 69%
See 1 more Smart Citation
“…This SHANK3 splicing mutation has been previously reported by (Li et al, ). SHANK3 variants named according to the SHANK3 RefSeq mRNA (NM_033517.1) and protein (NP_277052.1) sequence, in which the exon 11 sequence has been corrected.…”
Section: Methodssupporting
confidence: 69%
“…Fifteen causative variants (one splicing, six frameshift, and eight stop codon variants) are predicted to result in truncated proteins if escaping the nonsense‐mediated mRNA decay. The SHANK3 splicing variant has been shown to functionally impair mRNA splicing, producing an aberrant transcript containing an additional 77 bp intronic sequence (Li et al, ). Nine out of the 12 missense mutations were predicted pathogenic by the majority of computational methods, while pathogenicity predictions were discordant for three variants (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…To validate this finding, we examined 76 published case reports of affected individuals with pathogenic variants in a subset of 22 autism-associated genes for ID comorbidity (table 1 and online supplementary file 2). For example, recent case studies have identified autism co-occurring with ID in 21 individuals with de novo SHANK3 variants,19 19 individuals with NRXN1 variants20 and 18 individuals with TCF20 variants 21. Overall, 460 of 497 (92.6%) individuals with autism described in these studies had ID, emphasising that variants in these genes contribute to severe forms of autism with comorbid ID (table 1).…”
Section: Resultsmentioning
confidence: 86%
“…An important functional domain is the C‐terminal sterile alpha motif (SAM domain), which is required for multimerization and clustering of the protein at the synapse and is also essential for post‐synaptic targeting (Baron et al, 2006; Grabrucker, Vaida, Bockmann, & Boeckers, 2009). Truncated forms of Shank3, as observed in many patients (Li et al, 2018), lack the SAM domain and can therefore not be targeted to the synapse. In fact, two studies have observed that these shortened fragments of Shank3 are translocated to the nucleus (Cochoy et al, 2015; Grabrucker et al, 2014).…”
Section: Introductionmentioning
confidence: 99%